Formation of organic acids during cellobiose decomposition in hot-compressed water - Nazeri, G.; Liaw, S.; Yu, Y.; Wu, Hongwei (Elsevier Ltd, 2018)
Abstract This paper systematically reports the major organic acids produced during cellobiose decomposition in hot-compressed water (HCW) at 200–275 °C and a residence time of 8–66 s. Saccharinic, formic, lactic and glycolic acids are identified and quantified using high-performance anion exchange chromatography with conductivity detection and mass spectrometry (HPAEC-CD-MS). Among the identified organic acids, saccharinic acid, which is reported for the first time in the field under non-catalytic conditions, has the highest yield (i.e., ~5.8% at 275 °C and ~66 s) on a carbon basis, but formic acid has the highest contribution to total hydrogen ion in the liquid product due to its high molar concentration and high dissociation constant. The results also show that the hydrogen ion concentrations contributed by the identified organic acids agree well with those calculated from the measured pH of the solutions after the reaction, especially at cellobiose conversions <80%. The reaction pathways for the production of these organic acids during cellobiose decomposition in HCW are also summarised and discussed.